Impact of transgenerational host switch on gut bacterial assemblage in generalist pest, Spodoptera littoralis (Lepidoptera: Noctuidae) - Roy, Amit; Houot, Benjamin; Kushwaha, Sandeep; Anderson, Peter (Frontiers in Microbiology, 2023)
Diet composition is vital in shaping gut microbial assemblage in many insects. Minimal knowledge is available about the influence of transgenerational diet transition on gut microbial community structure and function in polyphagous pests. The current study investigated transgenerational diet-induced changes in Spodoptera littoralis larval gut bacteriome using 16S ribosomal sequencing. Our data revealed that 88% of bacterial populations in S. littoralis larval gut comprise Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes. The first diet transition experiment from an artificial diet (F0) to a plant diet (F1), cabbage and cotton, caused an alteration of bacterial communities in S.littoralis larval gut. The second transgenerational diet switch, where F1 larvae feed on the same plant in the F2 generation, displayed a significant variation suggesting further restructuring of the microbial communities in Spodoptera larval gut. F1 larvae were also challenged with the plant diet transition at the F2 generation (cabbage to cotton or cotton to cabbage). After feeding on different plant diets, the microbial assemblage of F2 larvae pointed to considerable differences from other F2 larvae that continued on the same diet. Our results showed that S.littoralis larval gut bacteriome responds rapidly and inexplicably to different diet changes. Further experiments must be conducted to determine the developmental and ecological consequences of such changes. Nevertheless, current study improves our perception of the impact of transgenerational diet switches on the resident gut bacteriome in S.littoralis larvae and could facilitate future research to understand the importance of symbiosis in lepidopteran generalists better.